Tingkat dan laju penurunan kualitas air di DAS Brantas Malang Raya - Perwira, Ima Yudha (Journal of Marine and Aquatic Sciences; Vol 5 No 2 (2019)DO - 10.24843/jmas.2019.v05.i02.p04, 2019)
The decrease level of water quality of Brantas Watershed in Malang Raya was observed in this study. The aim of this study was to observe the decrease level of water quality of Brantas Watershed from Batu to Malang City. This study was carried out in the Brantas Watershed of Malang Raya (8 stations: A, B, C, D, E, F, G, and H) for 18,4 Km. The water quality parameters observed in this study were: CODmn (permanganometry), CODcr (CODmn correlation based analysis), dissolved oxygen (DO) (Winkler iodometry), TDS and electrical conductivity (EC) (EC meter), pH (pH meter), and turbidity (Turbidity meter). The result showed the value of CODmn: 1,8-10,2 mg/L, CODcr: 5,6-31,5 mg/L, DO: 4,0-6,1 mg/L, TDS: 204-289 mg/L, EC: 430-617 µS/cm, pH: 7,1-7,6, and turbidity: 2,02-10,30 NTU. There are 3 stations (A, B, and C) with 1st class water quality, 1 station (D) with the 2nd class water quality, and 4 stations (E, F, G, and H) with 3rd class water quality. The decrease of water quality in the Brantas Watershed from Batu to Malang City was up to 3 times with a decrease rate of 2,3 mg/L-1Km-1. The decomposition of organic materials in the water of Batu City and western part of Malang City is relatively better than that of central parts of Malang City which might be caused by the over capacity of recovery (Self-purification mechanism).